Training in processing palm oil mushrooms into crackers in Delas Village, South Bangka - Muhammad Riski; Alika Larasati; Aisya Maulida; Nasywah Zulfa; Nisa Fitriyani; Khoirunnisa Azzahra Riefanti; Sahabudin Iqbal; Silvia Saputri; Fahria Fransisca Pilomulo; Muhammad Falatehan; Iis Juniati Lathiifah (Universitas Muhammadiyah Magelang, 2024)
Oil palm not only yields fruit but also facilitates the growth of palm mushrooms, a fungus that thrives around palm tree trunks. In Delas village, South Bangka, the primary source of livelihood for the community revolves around oil palm plantations. However, the fluctuating price of palm oil necessitates the exploration of alternative sources of income. In response, a service team has introduced processed food in the form of crackers made from palm mushrooms. The objective of this initiative is to educate and support the community in the process of turning palm mushrooms into crackers. This endeavor involved training sessions with members of PKK and BUMDes. As a result, partners have witnessed an improvement in their knowledge and skills in making crackers from palm mushrooms. This not only prevents the wastage of abundant mushroom production but also mitigates any adverse effects on the quality of palm oil production.